Perilaku Elit Politik Ala Selebriti - Ahmad Al Yakin (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2013)
Selebritisasi political phenomenon is rampant in Indonesia formulate study on the behavior of the political elite and the social meaning of waking up celebrity -style political behavior . Therefore, it is necessary to study to be formulated why political elites tend to use celebrity -style political maneuvering , which can contribute both theoretical and practical science . Political elite celebrity -style behavior is a phenomenon of the post-reform political pragmatism , is a product of socialization that comes as one of the factors that influence the behavior of the public and political choice . Society will impose their political choices based on information he received , which also turned out to be a political choice correlated with environmental conditions in which people lived . This makes the political choice of each person is different . Voters turn out to vote based on the information and knowledge gained about the party 's profile , figure candidates , as well as the vision and mission , but also there are voters turn out to vote despite the very minimal knowledge about the parties , candidates and also the vision and mission